COVID-19 disaster response: an emergency food and supply distribution programme in Bahía de Caráquez, Ecuador - Madison Searles; Andrew Jeffery; Yaa Takyiwaa, MPH; Breana Wonsey; David Cedeño; Christina Lupone, MPH; Avriel Diaz, MA (Elsevier, 2021)
Background: The COVID-19 pandemic has further challenged the world's most vulnerable populations' access to adequate food. The UN World Food Program estimates that COVID-19 will increase worldwide food insecurity from 135 million to 265 million people by 2021. In March, 2020, Walking Palms Global Health (WPGH) initiated their More than Food Emergency Relief Program in Bahía de Caráquez, Ecuador, working with local government to deliver food and supplies to at-risk households. We aim to assess how WPGH's response affected households early in the 2020 pandemic. Methods: Between March and July, 2020, rations were delivered to 225 families in rural, urban, and peri-urban communities within the city of Bahia de Caráquez located in the province of Manabí on Ecuador's west coast. These specific communities face frequent piped water disruptions, power outages, and mosquito-transmitted diseases such as dengue are endemic. In June, 2020, WPGH administered evaluations in the urban and rural communities, which included the World Food Program Food Confidence Score to address food consumption, food accessibility stress, and presence of chronic diseases. Findings: Evaluations were conducted in 21 of 45 urban households (47%) and 45 of 50 rural households (90%). Overall, 66 households (69%) completed surveys and 29 (31%) opted out. The association between household income before COVID-19 and food insecurity was significant (p=0·04). Before the first programme delivery, 59 participants (92%) worried that their household would experience food insecurity and most often felt nervous or stressed about possible food insecurity (n=55 [85%]). Insufficient access to food led to 55 respondents (85%) skipping meals. Food confidence scores remained stable over the pandemic's most challenging period (Food confidence score=37·68% before deliveries and 38·11% during deliveries). Respondents (n=61 [95%]) reported that boxes allowed them to prepare enjoyable and culturally appropriate meals. The most common combination of meals cooked with box items was rice and beans, stews, corviche, empanadas, and plantains with 98% of participants finding every box item useful. There was no relation between food insecurity and number of children (p=0·26) or number of people in households (p=1·00). There was no significant association between chronic disease and pre-COVID-19 household income (p=0·24) or respondents' food security (p=0·82). Interpretation: In communities that had high food insecurity before the pandemic, WPGH's response allowed households to maintain overall food consumption throughout the most challenging lockdown period. WPGH is currently working to innovatively and sustainably increase food security in the communities where they work. Limitations include programme administration relying on donor participation for financial support. Funding: None.